The Influence of Lifestyle on BMI Change for Tree-Month Injectable Hormonal Contraceptive Users - Asri Hikmatuz Zahroh; Muhammad Atoillah Isfandiari (Universitas Airlangga, 2015)
Three-month injectable hormonal contraception causes side effects of increasing Body Mass Index (BMI). This is one of the main reasons for acceptors to stop using injectable hormonal contraception for three months even though the increase in BMI is not experienced by all acceptors. There are other factors that can influence the increase in BMI, such as consumption habits, physical activity, and sedentary behavior. The purpose of this study was to determine the effect of lifestyle on changes in BMI on three-month injectable hormonal contraceptive acceptors. This research was an observational analytic study using a case-control design. Sampling using a simple random sampling technique. Analysis of the data used in this study is a simple logistic regression statistical test. The results showed that lifestyle factors that influence and risk of changes in BMI in three-month injectable hormonal contraceptive acceptors are sedentary behavior factors. Respondents with sedentary behavior 3 hours per day had a risk of 9.048 times greater to experience an increase in BMI compared to respondents with sedentary behavior of <3 hours per day. It was concluded that sedentary behavior influences changes in BMI on three months injectable hormonal contraceptive acceptors. By reducing sedentary behavior habits and improving exercise habits, three-month injectable hormonal contraceptive acceptors can reduce the risk of increased BMI.